Influence of intermittent hypoxic training on muscle energetics and exercise tolerance - Holliss, B. A.; Fulford, J.; Vanhatalo, A.; Pedlar, C. R.; Jones. A. M. (Journal of Applied Physiology, 2013)
Intermittent hypoxic training (IHT) is sometimes used by athletes to enhance nonhematological physiological adaptations to simulated altitude. We investigated whether IHT would result in greater improvements in muscle energetics and exercise tolerance compared with work-matched intermittent normoxic training (INT). Nine physically active men completed 3 wk of intensive, single-leg knee-extensor exercise training. Each training session consisted of 25 min of IHT (FiO2 14.5 ± 0.1%) with the experimental leg and 25 min of INT with the alternate leg, which served as a control. Before and after the training intervention, subjects completed a test protocol consisting of a bout of submaximal constant-work-rate exercise, a 24-s high-intensity exercise bout to quantify the phosphocreatine recovery time constant ([PCr]-t), and an incremental test to the limit of tolerance. The tests were completed in normoxia and hypoxia in both INT and IHT legs. Muscle metabolism was assessed noninvasively using 31P-magnetic resonance spectroscopy. Improvements in the time-to-exhaustion during incremental exercise were not significantly different between training conditions either in normoxia (INT, 28 ± 20% vs. IHT, 25 ± 9%; P = 0.86) or hypoxia (INT, 21 ± 10% vs. IHT, 15 ± 11%; P = 0.29). In hypoxia, [PCr]-t was speeded slightly but significantly more post-IHT compared with post-INT (-7.3 ± 2.9 s vs. -3.7 ± 1.7 s; P < 0.01), but changes in muscle metabolite concentrations during exercise were essentially not different between IHT and INT. Under the conditions of this investigation, IHT does not appreciably alter muscle metabolic responses or incremental exercise performance compared with INT.